2005
DOI: 10.1093/jxb/eri167
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed expression of the apoplastic ascorbate oxidase gene increases salt tolerance in tobacco and Arabidopsis plants

Abstract: Transgenic tobacco plants expressing the ascorbate oxidase (AAO) gene in sense and antisense orientations, and an Arabidopsis mutant in which the T-DNA was inserted into a putative AAO gene, were used to examine the potential roles of AAO for salt-stress tolerance in plants. AAO activities in the transgenic tobacco plants expressing the gene in sense and antisense orientations were, respectively, about 16-fold and 0.2-fold of those in the wild type. Under normal growth conditions, no significant differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
106
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(118 citation statements)
references
References 35 publications
11
106
0
1
Order By: Relevance
“…Therefore, the function of an enzyme catalyzing the waste (oxidation) of ascorbate (AsA) to reduce oxygen to water is quite hard to explain. AO over-expressing plants are prone to ozone [3] and salt [4] stresses, whereas lower expression apparently confers resistance to unfavorable environmental conditions [4]. Therefore, AO activity appears at best not necessary, if not even dangerous, and the silencing of AO genes seems a valuable strategy to increase AsA content in crops [5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the function of an enzyme catalyzing the waste (oxidation) of ascorbate (AsA) to reduce oxygen to water is quite hard to explain. AO over-expressing plants are prone to ozone [3] and salt [4] stresses, whereas lower expression apparently confers resistance to unfavorable environmental conditions [4]. Therefore, AO activity appears at best not necessary, if not even dangerous, and the silencing of AO genes seems a valuable strategy to increase AsA content in crops [5].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous reports have shown that different pathways are interconnected and together regulate the plant response to biotic and abiotic stresses (Ludwig et al, 2005;Ma et al, 2006). Abscisic acid and ethylene play an important role in the complicated story of abiotic stress and, consequently, cross-talk between these two kinds of plant hormone has been reported (Yamamoto et al, 2005). The relationship between polyamine and ethylene was complex.…”
Section: Discussionmentioning
confidence: 99%
“…Thus it is concluded that AO plays important role in modulating and maintaining the redox state and ratio of AA pool (Pignocchi et al, 2006). Besides, it was found that depressed expression of AO gene promoted AA accumulation in tomato fruit (Yamamoto et al, 2005).…”
Section: Introductionmentioning
confidence: 95%